Introduction to economics : theory and data - Jackson, Dudley (Toronto ; London : Macmillan, 1982)
"Introduction to Economics" equips its readers to handle data in economic analysis with confidence. The starting-point for the description and analysis of economic activity is value added - its production by labour and capital inputs and its distribution as income. The book explains these concepts and then describes how each sector of the economy gets its income, spends, save and acquires financial assets or liabilities.
Includes bibliographical references and Index.
aia 17/11/2017
Loans
Keywords: Economics